▼Gemcitabine for lung cancer. Issue 9 (September 1996) - Unknown
Abstract : The prognosis for most patients with lung cancer is poor. About 75% will have tumours of non-small-cell lung cancer (NSCLC) type and, at diagnosis, 4 out of 5 patients with NSCLC have either locally advanced or metastatic disease. Despite treatment, fewer than 1 in 10 of these people will be alive 5 years later. Gemcitabine (Gemzar - Lilly) has recently been licensed for the palliative treatment of adults with such late-stage cancers. It is promoted as a "new option in the management of NSCLC" with "no trade off between tumour remission and toxicity". What advantages does gemcitabine offer?